Św. Romanos Melodos - hymnos akathistos. Bizantyńska muzyka i poezja liturgiczna - Sowa, Wojciech (Vox Patrum, 1997)
The aim of this article is to show the poetry of Saint Romanos the Melodist, one of the greatest poets of the Byzantine Empire, the most probable autor of the Akathistos Hymnos - dedicated to the Blessed Virgin Mary, and to situate this lyric masterpiece in the Christian literary tradition, in the theology, and aesthetics.